Rapid weight loss in Olympic combat sports - Reale, R.; Slater, G.; Cox, G.; Burke, L. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Olympic combat sports separate athletes into weight divisions. Official weigh-ins are held 3-24h before competition to ensure no athlete is heavier than permitted. Athletes commonly engage in rapid weight loss (RWL), generally via body water manipulation, before weigh-in then attempt to restore losses before competition on the assumption that performance decrements can be reversed. The belief is that a size/strength/leverage advantage is gained by competing in a division lighter than habitual body mass (BM). Whether RWL improves the chance of success or not is unclear. Thus the aim of these investigations was to examine post weigh-in BM gain (a reflection of RWL) and competitive success. We also collected data on body composition and methods used to achieve and reverse RWL to determine the necessity and suitability of common practices. Methods: Olympic combat sport athletes (n=94) within 2w of competition had body composition assessed by dual energy x-ray absorptiometry and compared to weight division. Athletes (n=227) were surveyed on their aggressiveness of RWL and recovery habits via a previously validated questionnaire (Artiolli et al. 2009) which quantifies a rapid weight loss score (RWLS). Post weigh-in BM gain was measured in judo (n=86) and boxing (n=100) athletes at competitions and compared among a variety of sub groups. Results: All athletes were significantly heavier than their competitive weight division <2w before competition. Athlete calibre had an effect on RWLS (p=0.0042) however sport and sex did not. Differences in post weigh-in BM gain between winners and losers, and medallists and non-medallists in judo were significant at 0.9±0.3% (p=0.0021) and 1.4±0.4% (p=0.0026) respectively. Increased recovery time resulted in differences in post weigh-in BM gain in boxers of 0.37%(p=<0.0001). Surveys suggest athletes recognise the importance of recovery from RWL yet most do not understand optimal methods of recovery and rehydration. Discussion: Many combat sport athletes engage in RWL to make weight, as loss of body fat alone appears inadequate particularly for lighter athletes. Athletes favour combinations of passive/active dehydration and reduced food intake. Higher calibre athletes engage in more aggressive RWL than lower calibre athletes. A strong association between post weigh-in BM gain and success exists in judo which is not found in boxing, possibly due to the shorter recovery time prohibiting meaningful BM fluctuations or the different activity profiles of the sports. Fighters are keenly aware of the importance of recovery and re-hydration post weigh-in but are in need of support to optimise their practices.